Effects of mating on female reproductive physiology in the insect model, Rhodnius prolixus, a vector of the causative parasite of Chagas disease. - Jimena Leyria; Alessandra A Guarneri; Marcelo G Lorenzo; Marcela Nouzova; Fernando G Noriega; Samiha A M Benrabaa; Francisco Fernandez-Lima; Lilian Valadares Tose; Ian Orchard; Angela B Lange (Public Library of Science (PLoS), 2023)
The blood-sucking hemipteran Rhodnius prolixus is one of the main vectors of Chagas disease, a neglected tropical disease that affects several million people worldwide. Consuming a blood meal and mating are events with a high epidemiological impact since after each meal, mated females can lay fertile eggs that result in hundreds of offspring. Thus, a better knowledge of the control of R. prolixus reproductive capacity may provide targets for developing novel strategies to control vector populations, thereby reducing vector-host contacts and disease transmission. Here, we have used a combination of gene transcript expression analysis, biochemical assays, hormone measurements and studies of locomotory activity to investigate how mating influences egg development and egg laying rates in R. prolixus females. The results demonstrate that a blood meal increases egg production capacity and leads to earlier egg laying in mated females compared to virgins. Virgin females, however, have increased survival rate over mated females. Circulating juvenile hormone (JH) and ecdysteroid titers are increased in mated females, a process mainly driven through an upregulation of the transcripts for their biosynthetic enzymes in the corpus allatum and ovaries, respectively. Mated females display weaker locomotory activity compared to virgin females, mainly during the photophase. In essence, this study shows how reproductive output and behaviour are profoundly influenced by mating, highlighting molecular, biochemical, endocrine and behavioral features differentially expressed in mated and virgin R. prolixus females.